2015
DOI: 10.1002/ejoc.201501241
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylzinc‐Mediated Chlorolact­amization of Homoallylic Amines with Chloroform

Abstract: A novel chlorolactamization reaction of homoallylic amines has been developed. The treatment of homoallylic amines with dimethylzinc in chloroform led to the formation of the corresponding β‐chlorolactams via the Prins‐type cyclization of a carbamoyl chloride intermediate. The results of this study highlight the synthetic utility of chloroform as a source of both carbonyl group and chloride anion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…each) was treated with dimethylzinc (8 equiv.) in the presence of air . The desired indole‐3‐carboxamide 3aA was formed, albeit in low yield.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…each) was treated with dimethylzinc (8 equiv.) in the presence of air . The desired indole‐3‐carboxamide 3aA was formed, albeit in low yield.…”
Section: Resultsmentioning
confidence: 98%
“…Alternatively, in‐situ generation of phosgene[8a], [8b] provides a safer method, because highly reactive phosgene is consumed immediately by nucleophiles, ensuring low stationary concentrations , . We recently reported a novel method for in‐situ generation of phosgene from chloroform in the presence of dimethylzinc and O 2 , and its application to the chlorolactamization of homoallylic amines . As part of our program studying the utility of chloroform as a C1 unit,, we report a direct three‐component coupling of amine, indole, and phosgene generated in situ from chloroform via Friedel–Crafts‐type carbamoylation [Equation (4)].…”
Section: Introductionmentioning
confidence: 99%
“…Product 2a was formed by the cleavage of the C2–C3 bond followed by chlorine‐atom transfer. The examination of solvent effects showed that CHCl 3 was the best solvent . In fact, the reaction proceeded smoothly even at room temperature to afford 2a in 93 % yield (entry 4).…”
Section: Resultsmentioning
confidence: 99%
“…Nishida et al . (2016) has developed a chlorolactamization reaction of homoallylic amines with chloroform using dimethyl zinc catalyst (Scheme ) . Reaction starts with the oxidative decomposition of dimethyl zinc to form methyl and methoxy radicals which abstract hydrogen atom from chloroform to form trichloromethyl radical.…”
Section: Reaction Solvents As Precursors For the Installation Of Key mentioning
confidence: 99%